Neurological presentation of COVID-19: experience from a tertiary care hospital of Bangladesh - Islam, Md Rashedul; Rahman, Tanbin; Ahmed, Syed Mohaimeen; Khan, Mohammad Sakhawat Hossen; Azad, Md Rihan; Alam, Dilruba; Habib, Rumana (BIRDEM Medical Journal, 2020)
Background: Neurological manifestations of COVID-19 are being recognized day by day although predominant presentation is of respiratory illness. Understanding of impact of the virus on nervous system is important for selection and evolution of treatment now and in the future. The aim of the study was to describe the manifestations of COVID-19 affecting nervous system in a tertiary care hospital of Bangladesh Methods: This cross-sectional study was carried out in Department of Neurology, Bangladesh Institute of Research and Rehabilitation in Diabetes, Endocrine and Metabolic Disorders (BIRDEM) General Hospital from March, 2020 to October, 2020. Total forty patients who were admitted under neurology department were included in the study. Evidence of SARS-CoV-2 infection was confirmed in all the patients if RT-PCR of respiratory samples (eg, nasal or throat swab) was positive for viral ribonucleic acid (RNA). Clinical syndromes associated with COVID-19 were classified broadly as a cerebrovascular event, altered mental status and peripheral nervous system disorders. Data were collected on the basis of specific clinical case definitions. Results: Median age of the patients was 58.6 years (range 22–73). Among those, 26 (65%) were male and 14 (35%) were female. Twenty two (55%) of 40 patients presented with cerebrovascular event, of whom 15 (68%) had an ischaemic stroke, 5 (23%) an intracerebral haemorrhage. Two (9%) patients were diagnosed as cerebral venous sinus thrombosis on the basis of clinical presentation and magnetic resonance venography (MRV) finding. Apart from cerebrovascular events, 14 (35%) of 40 patients presented with altered mental status, comprising 9 (64%) patients with unspecified encephalopathy and 5 (36%) patients with encephalitis. Four (10%) patients were diagnosed as peripheral nervous system disorder among those 2 (50%) as Guillain-Barré syndrome (GBS) and 2 (50%) as Bell’s palsy. If we analyze the presenting features of the 40 patients, it is found that, 22 (55%) patients presented with headache, 20 (5%) with hemiparesis, 20 (50%) with speech problems, 19 (48%) with altered mental status, 10(25%) with facial asymmetry, 4 (10%) with seizure. Few percentages of patients presented with anosmia (10%), ageusia (5%) and quadriparesis (5%). Conclusion: Neurological involvement in COVID-19 is one of the major focuses of neurologist now a day. We have found cerebrovascular disese, encephalopathy and peripheral nervous system disorder as presentation of COVID-19 in our study. Prompt recognition of cases and early initiation of therapy will hasten better outcome of the patients. Neurological complications can cause permanent disability that will cost large scale health and economic burden. Further nationwide study is needed to quantify the association and disease burden. Birdem Med J 2020; 10, COVID Supplement: 33-40